2000
DOI: 10.3136/fstr.6.140
|View full text |Cite
|
Sign up to set email alerts
|

Selective Proliferation of Lactic Acid Bacteria and Accumulation of Lactic Acid during Open Fermentation of Kitchen Refuse with Intermittent pH Adjustment.

Abstract: When minced and autoclaved model kitchen refuse was inoculated with a small anrount of non-autoclaved model kitchen refuse as seed culture, incubated at 37'C for 3-5 days and intermittently pH neutralized, 27~5 g/1 of lactic acid was accumulated with a small amount of acetic acid and ethanol. The highest accumulation and highest productivity levels of lactic acid were observed at an initial and adjusted pH of 7.0 and a 6 h interval of pH adjustuent. After several hours of lag, the lactic acid bacteria became t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“…The dry mass of food waste was mainly composed of starch sugars, protein, fat and cellulose, which could be regarded as a suitable substrate for ethanol production. These characteristics were very similar to others that have been reported (Sakai et al 2000;Shin et al 2004;Tang et al 2008). Figure 1a shows the enzymatic digestibility index has increased from 0.73 to 0.78 after 2.5 h of enzymatic hydrolysis with the increase of glucoamylase concentration from 80 to 100 u/g food waste, and 0.1 increase of digestibility index was found when glucoamylase concentration increased further to 120 u/g food waste.…”
Section: Characteristics Of the Food Waste Mixturesupporting
confidence: 78%
“…The dry mass of food waste was mainly composed of starch sugars, protein, fat and cellulose, which could be regarded as a suitable substrate for ethanol production. These characteristics were very similar to others that have been reported (Sakai et al 2000;Shin et al 2004;Tang et al 2008). Figure 1a shows the enzymatic digestibility index has increased from 0.73 to 0.78 after 2.5 h of enzymatic hydrolysis with the increase of glucoamylase concentration from 80 to 100 u/g food waste, and 0.1 increase of digestibility index was found when glucoamylase concentration increased further to 120 u/g food waste.…”
Section: Characteristics Of the Food Waste Mixturesupporting
confidence: 78%
“…L. rhamnosus, which is an l-forming homo-fermentative strain, was then inoculated into the treated refuse paste. As reported previously (Sakai et al 2000), nutrientrich food waste appears to be a superior growth medium for fastidious lactic acid bacteria that generally require a variety of nutritional elements. The amount of water added was minimized to reduce energy input for its distillation from the fermented broth; an equal proportion of water to refuse was sufficient to yield the highest productivity of l-lactic acid.…”
Section: L-lactic Acid Fermentation Under Semisolid Conditionsmentioning
confidence: 76%
“…Direct composting and methane fermentation, which produce fertilizers and biogas, are alternative ways to reuse food waste, but these processes have been applied only in rural areas. On the other hand, our previous study, which aimed to develop an economical means of converting solid domestic and industrial food wastes into valuable products, showed that municipal food waste is a good source of natural lactic acid bacteria (Sakai et al 2000). This finding indicated another route of food waste reuse suitable for use in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most practical biological treatments is anaerobic digestion. It is a great tool to stabilize a large volume of waste materials economically and effectively (Sakai et al, 2000). It also produces low biomass and is able to destroy pathogens (Banarjee et al, 1999).…”
Section: Introductionmentioning
confidence: 99%